O habeas corpus no Brasil até a reforma constitucional de 1926: a doutrina brasileira do writ no Ceará - Travassos, Mayara de Andrade Santos (2019)
The present work aimed to analyze the Habeas Corpus in its historical perspective. To this end, an investigation was made regarding the uses of this instrument, from the moment of its enthronement into the Brazilian legal system in 1832, taking into consideration also its insertion in the Federal Constitution of 1891, which culminated in the extension of its use until 1926, date of the constitutional reform that restricted its application. The research was divided into three chapters, in which, initially, was developed an overview of the Habeas Corpus Doctrine in Brazil until the referred constitutional reform. In the second part, some political issues that were judicialized through the use of this writ were analyzed, in several federative states, and in this context, judgments of the Federal Supreme Court were also examined. Finally, the last chapter aimed to investigate the use of the Habeas Corpus in the state of Ceará, based not only on the analysis of political facts, but also on the study of judgments and lawsuits filed in the Court of Justice of the State of Ceará and in the local Public Archive. Thus, it was concluded that there was an inclination for the use of the aforementioned constitutional remedy in a broader way by political authorities, that is, in this temporal interstice, it was noticed a decrease in the use of this instrument, in regard to the expansion of the Habeas Brazilian Doctrine Corpus, by the population of Ceará in general. The methodology used was the descriptive-analytical, developed, in what pertains to the type, through bibliographic research, being qualitative and descriptive regarding the objectives.